Public sources of information and information needs for pandemic Influenza A (H1N1) - Wong, Li Ping; Sam, I-Ching (Springer, 2010)
Providing health information during disease outbreaks is a fundamental component of outbreak control strategies. This study aimed to explore sources of influenza A(H1N1)-related information, specific information needs and preferences of the lay public during the peak of the outbreak. A cross-sectional, population-based, computer-assisted telephone interview of 1,050 respondents was conducted in Malaysia between July 11 and September 12, 2009. Newspaper, television and family were three main sources of information about A(H1N1). There were substantial ethnic differences; the Malays were significantly more likely to identify television as main source, while newspapers and family were identified as the main sources by the Chinese and Indians, respectively. Overall, the two main information needs identified were prevention and treatment. The Malays expressed lesser need for overall information than other ethnic groups. The three most preferred sources of information were television, newspapers and healthcare providers. There were significant positive correlations between amount of information received with knowledge (r = 0.149), perceived susceptibility to infection (r = 0.177), and other behavioral responses. Health information dissemination should be dedicated to meeting the information needs of diverse sociodemographic and ethnic groups. The findings highlight the importance of providing information that increases awareness and behavioral changes in disease prevention yet reduce fear.